(untitled) (Práxis Educativa, 2026)
This article addresses technical and ethical aspects of Cognitive Computing, which simulates human cognitive abilities, known by the codename “Artificial Intelligence” (AI), pointing out semantic inconsistencies generated by the anthropomorphization of machine architectures, which reinforces the belief in the intellectual superiority of these purely stochastic computer programs. With a propositional approach, it’s argued that it is possible to shape this praxis in favor of a technologised education that makes use of Machine Learning (ML) to achieve high performance in the education of digital natives, with practices that update the classical notion of Greek paideia. A descriptive and deductive methodology is adopted, critically analysing authoritative scientific sources on the subject, with contributions from the Philosophy of Technology. The research presents relevant results regarding the characterology of AI, eliminating misconceptions and mythifications about its real potential, as well as bringing to the pedagogical debate the possibility of its adoption to implement a technopaideia appropriate to the demands of the digital age. Keywords: Artificial intelligence. Ethics. Technopaideia.